2021
DOI: 10.1155/2021/6454177
|View full text |Cite
|
Sign up to set email alerts
|

Role of IL‐37‐ and IL‐37‐Treated Dendritic Cells in Acute Coronary Syndrome

Abstract: As a chronic inflammatory disease, atherosclerosis is a leading cause of morbidity and mortality in most countries. Inflammation is responsible for plaque instability and the subsequent onset of acute coronary syndrome (ACS), which is one of the leading causes of hospitalization. Therefore, exploring the potential mechanism underlying ACS is of considerable concern, and searching for alternative therapeutic targets is very urgent. Interleukin-37 (IL-37) inhibits the production of proinflammatory chemokines and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 101 publications
(151 reference statements)
0
12
0
Order By: Relevance
“… 62 , 63 IL-37 also mediated lipid metabolism via the IL-1R8/TLR4/NF-κB signaling pathway to reduce MI. 64 In conclusion, IL-37 influences CD4+ T cell typing, promotes macrophage transformation and regulates lipid metabolism during MI. The IL-37 amplification of Tregs is similar to the IL-33/ST2 signaling pathway and research is necessary to demonstrate whether these two cytokines engage in cross-talk.…”
Section: Regulation Of Interleukin-1 Family In Cardiovascular Diseasesmentioning
confidence: 94%
See 1 more Smart Citation
“… 62 , 63 IL-37 also mediated lipid metabolism via the IL-1R8/TLR4/NF-κB signaling pathway to reduce MI. 64 In conclusion, IL-37 influences CD4+ T cell typing, promotes macrophage transformation and regulates lipid metabolism during MI. The IL-37 amplification of Tregs is similar to the IL-33/ST2 signaling pathway and research is necessary to demonstrate whether these two cytokines engage in cross-talk.…”
Section: Regulation Of Interleukin-1 Family In Cardiovascular Diseasesmentioning
confidence: 94%
“…62,63 IL-37 also mediated lipid metabolism via the IL-1R8/TLR4/NF-κB signaling pathway to reduce MI. 64 In conclusion, IL-37 influences CD4+ T cell typing, promotes macrophage transformation and regulates lipid metabolism during MI. The…”
Section: Myocardial Infarctionmentioning
confidence: 94%
“…Excessive effective T cells and insufficient recruitment of Treg cells can lead to malignant ventricular remodeling after MI (68). The ability of IL-37-induced DCs to activate naive T cells and induce Treg cells has been reported (69), whereas tolerant DCs induced by IL-38 and TnI show stronger tolerance (10). We found that IL-38 inhibited LPS-induced maturation of DCs, thus resulting in lower expression of cell surface molecules and inflammatory factors than that in LPS-induced DCs that were not treated with IL-38 (10).…”
Section: Interleukin-38 Ameliorates Malignant Ventricular Remodeling ...mentioning
confidence: 99%
“…Furthermore, it was also reported that overexpression of IL-37 significantly increases plaque instability in ApoE -/- mice ( 14 ). Furthermore, in vitro experiments demonstrated that IL-37 attenuated atherosclerosis by suppressing T cell activation, inducing the response of regulatory T cells and inhibiting vascular calcification ( 11 , 15-17 ). However, to the best of our knowledge, the effect and underlying mechanism of IL-37 on diabetic atherosclerosis remains unclear.…”
Section: Introductionmentioning
confidence: 99%